2018
DOI: 10.1128/mbio.01839-18
|View full text |Cite
|
Sign up to set email alerts
|

Erratum for Penewit et al., “Efficient and Scalable Precision Genome Editing in Staphylococcus aureus through Conditional Recombineering and CRISPR/Cas9-Mediated Counterselection”

Abstract: The first name of the third author was misspelled. The name should appear as shown above.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Although RecT homologs have demonstrated more cross‐species activity, RecE appears to show more limited activity in an evolutionarily distant species . The Rpsl and RpoB mutagenesis‐based evaluation workflow facilitates the activity assessment of various RecTs, which will contribute to RecT‐assisted ssDNA recombineering‐related genetic engineering and, additionally, enrich the library of molecular genetic elements for Lactobacillus genome editing. However, a genome‐wide survey of RecE/T association will still be challenging for some species without an endogenous phage.…”
Section: Discussionmentioning
confidence: 99%
“…Although RecT homologs have demonstrated more cross‐species activity, RecE appears to show more limited activity in an evolutionarily distant species . The Rpsl and RpoB mutagenesis‐based evaluation workflow facilitates the activity assessment of various RecTs, which will contribute to RecT‐assisted ssDNA recombineering‐related genetic engineering and, additionally, enrich the library of molecular genetic elements for Lactobacillus genome editing. However, a genome‐wide survey of RecE/T association will still be challenging for some species without an endogenous phage.…”
Section: Discussionmentioning
confidence: 99%
“…When using synthetic single‐strand oligonucleotides as a repair template, the auxiliary recombination system can be simplified, utilizing the SSAP only (Table S1, Supporting Information). Studies have indicated that λ Bet is not a versatile SSAP, which only retains function in some Proteobacteria species . In contrast, RecT efficiently mediates recombination in some gram‐positive bacteria .…”
Section: Repair Of Dna Double‐strand Breakmentioning
confidence: 99%
“…Intriguingly, although they function similarly and share close quaternary structure, their sequence similarities are poor, indicating that they may evolve independently but convergently, posing a challenge in identifying new SSAPs for CRISPR‐based genome editing. A recent study had screened an array of SSAPs to identify one for establishing a CRISPR‐based genome editing method in S. aureus , which allows the usage of short ssDNA as a repair template . The authors found five SSAPs, including λ Bet, three putative SSAPs originated from S. aureus , and a predicated SSAP from Legionella pneumophilia , barely worked in S. aureus , whereas only one SSAP, termed EF2132, derived from Enterococcus faecalis , efficiently rescued the bacteria from lethal genome targeting in S. aureus using short ss oligos as repair templates.…”
Section: Repair Of Dna Double‐strand Breakmentioning
confidence: 99%
See 2 more Smart Citations